Optimized low-temperature fabrication of WO3 films for electrochromic devices. (26th October 2017) - Bae, Jaehyun; Seo, Dong Gyu; Park, Su Mi; Park, Kyu Tae; Kim, Haekyoung; Moon, Hong Chul; Kim, Se Hyun
Abstract: We investigated the effect of process conditions on the electrochromic (EC) properties of tungsten trioxide (WO3 ) films. When WO3 films deposited using a sol-gel method were thermally treated in air at 150 °C, the majority of tungsten species in the films became W 6+, which is important for the realization of an optically transparent bleached state. On the other hand, annealing in a vacuum required only 60 °C to induce a similar level of W 6+ in the WO3 films. However, a cracked film morphology was observed at higher temperatures, regardless of whether the films were annealed in air or vacuum. Using the WO3 films prepared under various conditions, EC devices (ECDs) were fabricated to evaluate EC properties. We concluded that the optimal annealing conditions for WO3 films for ECDs are 60 °C in vacuum, at which the highest coloration efficiency, largest transmittance difference, and fastest bleaching/coloration dynamics were obtained. These mild fabrication conditions at a low temperature (60 °C) provide the opportunity to utilize flexible electrodes on plastic. Therefore, we successfully demonstrated a flexible WO3 -based ECD.